Identify the risk factors for anemia among 6 to 24 months old children in eastern province - Arun, J.; Peiris, D.R.; Miralan, V. (University of Jaffna, 2012)
The prevalence of anaemia among children aged between 6 to 24 months remains relatively high (48%) in Sri Lanka. Identification of the anaemic risk factors among children is important to develop appropriate interventions. The aim of the present study was to identify the risk factors for anemia among 6 to 24 month old children in eastern province. The present study was conducted as a cross-sectional study in Batticalo and Ampara districts. A sample of 456 subjects aged between 6 to 24 months children were selected using a cluster random sampling method. A pre tested structured interviewer administrated questionnaire was used to identify the risk factors associate with anaemia among children. Socio economic (SE), child feeding practices (CFP), mother nutrition knowledge (MNK), communicable diseases on previous month (CDPM), water, sanitation and home gardening practices (WSH), and mother and child nutrition status (MCN) were considered as 6 main indicators to identify the risk factors. The HaemoCue method was used to measure haemoglobin concentration, and anaemia was defined as haemoglobin <11g/dl. Weight and height were taken to assess the nutrition status of the children. A single 24 hour recall was also performed to assess nutrient intake of the children. The overall prevalence of anaemia among the study group was 79% and 4% was severely anaemic. SE, CFP, MNK, CDPM, WSH, MCN indicators were identified as risk factors for anaemia and they were significantly associated (p<0.01) with low hemoglobin levels among the children. Dietary iron intake from the food of non anaemic children was significantly higher than anaemic children. In conclusion Factors that were significantly associated with anaemia were socio economic, child feeding practices, mother nutrition knowledge, communicable diseases, water, sanitation and home gardening , and mother and child nutritional status. CFP and SE indicators were strongly associated with anaemic children than other indicators.
Keywords: Socio economic; Anaemia; Children; Haemoglobin; Assessment